QTAIM Analysis of the Bonding in Pyridyl- N-Heterocyclic Carbene Triruthenium carbonyl cluster: [Ru3(μ-H)(μ-κ3C2,N-pyCH2 ImMe) (CO)9] (ImMe=3-methylimidazol-2- ylidene) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The bonding in the pyridyl N-Heterocyclic Carbene Triruthenium carbonyl cluster [Ru3(μ-H)(μ-κ3C2,N-pyCH2ImMe)(CO)9] is explored using the Quantum Theory of Atoms-in-Molecules (QTAIM). The metal–metal and metal–ligand bond critical points properties are ρ(r), ∇2ρ(r), H(r), G(r) and ellipticity. Also the bond delocalization indices δ(A, B), are correlated with the data from previous studies of the organometallic systems. These results have allowed a comparison between topological properties of different atom-atom interactions. At the core of triruthenium cluster, Ru3H part, the topological data recognize the existence of a bond path in only two of the Ru(1)-Ru(2) and Ru(1)-Ru(3) edges, and there is no direct bond path has been found for the interaction between the hydride bridged Ru atoms, although a non-negligible delocalization index δ(Ru(2)...Ru(3)) has been obtained for this non-bonding interaction. A multicenter 4c–4e interaction is proposed to exist in the core part, Ru3H. All topological parameters are calculated for the two existing Ru-C bonds between the ruthenium atoms and the pyridyl and NHC ligands are similar, and they confirm that these interactions are pure σ bond. The analysis of the topological parameters of the NHC and pyridyl ligands bonds confirm the existence of π-electron delocalization within the six-membered ring of pyridyl ligand and hindered π-electron delocalization within the five-membered ring of NHC ligand with some double-bond character in the interaction of the carbine C atom with the adjacent N atoms.